Irrigation Water Productivity of Basmati Rice; An On-Farm Comparison Between Rice Grown With Drip and Conventional Flood Methods of Irrigation. - Soman, P.; Bhardwaj, A. K.; Heierli, Urs; Labh, B. K. (European Journal of Applied Sciences, 2021)
In this on farm study, drip irrigation systems were installed in 21 farmers’ fields in 1 acre area each, where rice is grown conventionally by flood irrigation. Pan E based irrigation schedule is followed in the drip treatments. A fertigation schedule is also implemented for fertilizer application in the drip irrigated fields. A comparison between conventional flood and drip method of irrigations were done on data of Irrigation water consumption, rice grain yield and irrigation water productivity (IWP). Overall hike in yield because of drip method of irrigation was 10-18 % of that in flood and mean IWP were 0.8 kg/m3 in drip and 0.3 kg/m3 in flood irrigated field.